Drinking water and blood pressure: some aspects of problem in republic Dagestan - S. O. Abdulkadyrova; G. E. Gadzhiev; kh. G. Omarova (Юг России: экология, развитие, 2015)
The aim of this study was to estimate the links between chemical composition of drinking water and a level of arterial pressure (AP) and prevalence of an arterial hypertension AH) in populations in highmountainous (Kulinsky,Tljaratinsky, Tsuntinsky areas) and plane regions (Nogajsky area ) of republic Dagestan. Drinking water in high-mountainous region was low mineralized (128, 24±7, 41 mg /l). A parity of anions was HCO3SO4 CL, the parity of cations was Сa>Mg>Na. In plane region drinking water was more mineralized (633, 26±22, 56 mg /l) the parity of anions was HCO3 > SO4 > Cl and the parity of cations was Na> Ca> K> Mg. It was revealed, that in a high-mountainous region agerelated levels of AP were lower, than that in plane region. Age increase of BP was negligible. Prevalence AH (BP≥140/90 mm Hg) in high-mountainous areas was accordingly equal 5,67±0,48 %., 4,21±0,93 %, 7,23±0,73 %. In Nogajsky area the prevalence of AH was equal 26,90±0,92 %.